PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, DAN KEPEMILIKAN SAHAM PUBLIK TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Pada Perusahaan Makanan dan MinumanYang Terdaftar Di Bursa Efek Indonesia Periode 2014-2017) - Dirvi Surya Abbas; Mohamad Zulman Hakim; Nur Istianah (COMPETITIVE, 2019)
The purpose of this study is to determine the effect of Profitability proxied by Return On Assets (ROA), Firm Size, Leverage proxied by Debt to Equity Ratio (DER), and Public Share Ownership (KSP) on Corporate Social Responsibility Disclosures in food and beverage companies which is listed on the Indonesia Stock Exchange (IDX). The research period used is 4 years, namely the period 2014-2017.The population of this study includes all food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period. The sampling technique uses purposive sampling technique. Based on predetermined criteria obtained 8 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis.The results showed that partially profitability proxied by Return On Assets (ROA), Company Size (SIZE) had a positive effect on Disclosure of Corporate Social Responsibility and Public Share Ownership negatively affected the Disclosure of Corporate Social Responsibility. Whereas Leverage proxied by Debt to Equity Ratio (DER) states that the results have no effect on Corporate Social Responsibility Disclosures.